KORONA DAN IMAN AKAN ALLAH (Telaah Filsafat Ketuhanan, Sebuah Teodise ) - Albinus Lonek (Program Studi Filsafat Agama Universitas Katolik Widya Mandira Kupang, 2021)
Covid19, is a fact that deeply disturbs so many people. The anxiety of the Covid 19 is not because it attacks the human respiratory system and destroys our immune system, but it kills everyone (humans). Even to put it plainly, the corona is something that is above humans. The fact is clear, until now, he is still a boomerang for humans. Corona that is so fierce makes so many perceptions scattered among the public. Some project the corona with a postmodern